Die Korrespondenz des Ministers für Cultus und Unterricht Leo Thun-Hohenstein (1849-1860). Auswahledition: Zu den Reformen von Unterricht und Bildung in der Habsburgermonarchie - Aichner, Christof (2022)
The book publishes for the first time private letters from an to Leo Thun-Hohenstein, minister of education 1849-1860. In this periode Thun profoundly reformed the Austrian educational system.